2008
DOI: 10.1111/j.1523-5378.2008.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori

Abstract: The different invasive and noninvasive diagnostic tests for Helicobacter pylori have been applied mainly in emerging countries. Molecular methods have been developed, especially a test for detection of H. pylori and its clarithromycin resistance directly from stools. The long-term effects of eradication on histologic lesions have been studied in a meta-analysis and the prognostic value of post-treatment in gastric mucosa-associated lymphoid tissue lymphoma has been assessed. An operating link for gastritis ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
(60 reference statements)
1
15
0
4
Order By: Relevance
“…The rapid stool test is based on the same monoclonal antibody as the monoclonal EIA which was used for comparison. Our results confirmed the excellent performance of the monoclonal EIA both pre-and posttreatment in pediatric patients (8,9,15). All published trials with children using the monoclonal EIA consistently showed values of Ն95% for sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 85%
“…The rapid stool test is based on the same monoclonal antibody as the monoclonal EIA which was used for comparison. Our results confirmed the excellent performance of the monoclonal EIA both pre-and posttreatment in pediatric patients (8,9,15). All published trials with children using the monoclonal EIA consistently showed values of Ն95% for sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 85%
“…13,14 Trials conducted in various epidemiological settings consistently associated GC with OLGA stages III ⁄ IV. [15][16][17] Pepsinogens are proteolytic enzymes produced by gastrointestinal epithelia: pepsinogen I (PgI) is virtually found only in the gastric corpus, whereas pepsinogen II (PgII) is produced by both antral and oxyntic epithelia. Gastric mucosal atrophy results in a (progressive) decline in both serum PgI and the PgI ⁄ PgII ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive test are endoscopy, culture, molecular methods, 11 These sensitivity and specificity are not worse, but even better than those of other recent non-invasive methods. 10 A limitation of this method is that it does not discriminate between current and old infection as it is a serology test. 12 But, although the endoscopic biopsy and urea breath test are useful for active GI infection, they are not completely reliable for nondigestive disease.…”
Section: Discussionmentioning
confidence: 99%